Low Emissions Food Systems Initiative in Kenya - Cramer, Laura K. (International Livestock Research Institute, 2023)
A poster describing the activities of the Low Emissions Food Systems initiative in Kenya. Working closely with key actors to provide knowledge, information, and tools needed to make robust evidence-based decisions to reduce food systems emissions